Influence of the end cap deformation of a hollow transmission bar on the hollow split Hopkinson pressure bar test results. (February 2018) - Feng, Jie; Jiang, Mingfei; Xu, Hui; Li, Zhongxin; Wu, Zhilin
Highlights: The error caused by end cap deformation in hollow split Hopkinson bar test is proposed. The frequency of the disturbance in test result is similar to that of the end cap vibration. The end cap vibration disappears when then the thickness of end cap is equal or greater than half internal diameter of a hollow transmission bar. Abstract: The deformation of an end cap was found when analyzing a hollow transmission bar with an end cap. The deformation may cause errors in hollow split Hopkinson pressure bar (SHPB) test results. Therefore, the influence of the end cap deformation on hollow SHPB test results was analyzed to guide researchers to avoid these mistakes. It is known that the hollow split Hopkinson pressure bar technique using a hollow transmission bar with an end cap is a material dynamic property testing technology, which is used to increase the amplitude of the transmitted signal by reducing the transmission bar cross-sectional area. The relation between the end cap deformation and the test results was derived. And the natural frequency of an end cap was also calculated to compare with the frequency of the interferences in test results. Several simulations and hollow SHPB experiments using hollow transmission bars with end caps in different thickness were undertaken to analyze the influence of the end cap deformation on Hopkinson bar test results. A high-frequency interference was found in a transmitted wave when the end cap was vibrating which also conform the analyzed relation between them. High-frequency interferences were also found in the experiments. The frequency of the interference in a transmitted wave (in both simulations and experiments) was similar to the natural frequency of the end cap. The vibration and the interference became weak and the interference frequency became high when the thickness of an end cap increased. When the thickness of an end cap was larger than half external diameter of the hollow transmission bar, both the vibration and the interference disappeared, however the transmitted wave introduced another kind of distortion.